2019
DOI: 10.3389/fimmu.2019.02177
|View full text |Cite
|
Sign up to set email alerts
|

1-Palmitoyl-2-Linoleoyl-3-Acetyl-rac-Glycerol (PLAG) Rapidly Resolves LPS-Induced Acute Lung Injury Through the Effective Control of Neutrophil Recruitment

Abstract: Acute lung injury (ALI) is an acute respiratory failure that is associated with excessive neutrophil recruitment and high mortality. To assess the efficacy of 1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol (PLAG) as a therapeutic agent for ALI, this compound was administered orally to mice challenged with an intranasal dose of lipopolysaccharide (LPS). Using this model, we found that PLAG promotes resolution of ALI through effective control of LPS-induced neutrophil infiltration, endothelial permeability, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Neutrophils are also vital components of the inflammatory response that characterizes ALI, and are considered to be the final effector cells that responsible for lung injury due to their ability to express multiple cytotoxic products (Li et al 2019;Pinheiro et al 2019). Myeloperoxidase (MPO), which is localized in the primary granules of neutrophils (Lee et al 2019), reflects the adhesion and migration of neutrophils in lung tissues. In this study, LPS promoted the level of MPO, but hesperetin and Dex reversed the result.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are also vital components of the inflammatory response that characterizes ALI, and are considered to be the final effector cells that responsible for lung injury due to their ability to express multiple cytotoxic products (Li et al 2019;Pinheiro et al 2019). Myeloperoxidase (MPO), which is localized in the primary granules of neutrophils (Lee et al 2019), reflects the adhesion and migration of neutrophils in lung tissues. In this study, LPS promoted the level of MPO, but hesperetin and Dex reversed the result.…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity of PLAG in the regulation of MSU-induced CXCL8 expression is associated with its control ability of P2Y6 receptor endocytosis. Previously, we demonstrated that PLAG accelerates the termination of LPS-induced TRAM and TRIF-dependent TLR4 signaling, resulting in the reduced IRF3-dependent CXCL8 expression (49). In the study, PLAG did not affect MyD88-mediated NF-κB activation that induces the transcriptional expression of IL-1β.…”
Section: Discussionmentioning
confidence: 53%
“…In the previous study, PLAG induced rapid resolution of inflammation in LPS-induced acute lung injury via early elimination of LPS and early termination of endocytosisdependent signaling of TLR4 (49). PLAG remarkably ameliorated LPS-induced acute lung injury, which is a disease caused by a PAMP molecule (49). In this study, we examined a mitigating effect of PLAG on gouty inflammation, one of the sterile inflammations caused by MSU crystal, a substance thought to be DAMP.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intratracheal injection of LPS stimulates alveolar macrophages’ rapid production of proinflammatory cytokines like TNF-α, IL-6 and IL-1β, which induce the infiltration and activation of neutrophils ( Bosmann et al, 2013 ; Chen et al, 2020 ; Chignard and Balloy, 2000 ; de Souza Xavier Costa et al, 2017 ; Rittirsch et al, 2008 ). Stimulated neutrophils then produce a large quantity of ROS and cytokines, which further aggravate severe lung damage through destructive inflammatory responses ( Dong and Yuan, 2018 ; Lee, H.R. et al, 2019 ; Potey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%